2022
DOI: 10.1073/pnas.2115566119
|View full text |Cite
|
Sign up to set email alerts
|

Sideroflexin 4 is a complex I assembly factor that interacts with the MCIA complex and is required for the assembly of the ND2 module

Abstract: Significance Mitochondria are double-membraned eukaryotic organelles that house the proteins required for generation of ATP, the energy currency of cells. ATP generation within mitochondria is performed by five multisubunit complexes (complexes I to V), the assembly of which is an intricate process. Mutations in subunits of these complexes, or the suite of proteins that help them assemble, lead to a severe multisystem condition called mitochondrial disease. We show that SFXN4, a protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Homologs of MTCH2 are present in metazoan peroxisomes and its orthologs are found throughout holozoa, suggesting that the MTCH2 family has co-opted the SLC25 transporter fold to function in diverse biological membranes. This type of functional divergence has been previously described for SFXN4 and ATP13A1, both transporter family proteins that have evolved biogenesis or dislocase functions, respectively (18, 24, 39).…”
Section: Main Textsupporting
confidence: 61%
“…Homologs of MTCH2 are present in metazoan peroxisomes and its orthologs are found throughout holozoa, suggesting that the MTCH2 family has co-opted the SLC25 transporter fold to function in diverse biological membranes. This type of functional divergence has been previously described for SFXN4 and ATP13A1, both transporter family proteins that have evolved biogenesis or dislocase functions, respectively (18, 24, 39).…”
Section: Main Textsupporting
confidence: 61%
“…The SFXN1 physical interactors identified here suggested that SFXN1 could be in the vicinity of respiratory complexes I and IV. SFXN4 was recently shown to act as an assembly factor for complex I, interacting with the mitochondrial complex I intermediate assembly (MCIA), which contains TMEM126B [ 62 ]. Amongst the FXN1 partners identified in this study, TMEM126A and TIMMDC1 are two complex I assembly factors interacting with MCIA [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…SFXN1 physical interactants identified here permit to link SFXN1 to complex I and complex IV suggesting that SFXN1 is in the vicinity of respiratory complexes. SFXN4 was recently shown to act as an assembly factor for the complex I interacting with the mitochondrial complex I intermediate assembly (MCIA) which contains TMEM126B [60]. Amongst SFXN1 partners we identified, TMEM126A and TIMMDC1 are two complex I assembly factors interacting with MCIA [61,62].…”
Section: Discussionmentioning
confidence: 90%